SOX17 regulates uterine epithelial–stromal cross-talk acting via a distal enhancer upstream of Ihh. Issue 1 (December 2018) - Wang, Xiaoqiu; Li, Xilong; Wang, Tianyuan; Wu, San-Pin; Jeong, Jae-Wook; Kim, Tae; Young, Steven; Lessey, Bruce; Lanz, Rainer; Lydon, John; DeMayo, Francesco
Abstract Mammalian pregnancy depends on the ability of the uterus to support embryo implantation. Previous studies reveal theSox17 gene as a downstream target of thePgr- Gata2-dependent transcription network that directs genomic actions in the uterine endometrium receptive for embryo implantation. Here, we report that ablatingSox17 in the uterine epithelium impairs leukemia inhibitory factor (LIF) and Indian hedgehog homolog (IHH) signaling, leading to failure of embryo implantation. In vivo deletion of the SOX17-binding region 19 kb upstream of theIhh locus by CRISPR-Cas technology reducesIhh expression specifically in the uterus and alters proper endometrial epithelial–stromal interactions, thereby impairing pregnancy. This SOX17-binding interval is also bound by GATA2, FOXA2, and PGR. This cluster of transcription factor binding is common in 737 uterine genes and may represent a key regulatory element essential for uterine epithelial gene expression. The transcription factor SOX17 is important for uterine gland formation, fertility, and embryo implantation in mouse. Here the authors show that SOX17 is upstream of Indian hedgehog to regulate mouse uterine receptivity, and their analysis of uterine tissue from endometriosis patients suggests the same function in humans.